Imaging Subduction Beneath Mount St. Helens: Implications for Slab Dehydration and Magma Transport. Issue 6 (21st March 2019) - Mann, Michael Everett; Abers, Geoffrey A.; Crosbie, Kayla; Creager, Kenneth; Ulberg, Carl; Moran, Seth; Rondenay, Stéphane
Abstract: Mount St. Helens (MSH) is anomalously 35–50 km trenchward of the main Cascade arc. To elucidate the source of this anomalous forearc volcanism, the teleseismic‐scattered wavefield is used to image beneath MSH with a dense broadband seismic array. Two‐dimensional migration shows the subducting Juan de Fuca crust to at least 80‐km depth, with its surface only 68 ± 2 km deep beneath MSH. Migration and three‐dimensional stacking reveal a clear upper‐plate Moho east of MSH that disappears west of it. This disappearance is a result of both hydration of the mantle wedge and a westward change in overlying crust. Migration images also show that the subducting plate continues without break along strike. Combined with low temperatures inferred for the mantle wedge, this geometry greatly limits possible source regions for mantle melts that contribute to MSH magmas and requires lateral migration over large distances. Plain Language Summary: Subducting oceanic plates are heated as they descend into the Earth and release fluids, generating magma that feeds overlying arc volcanoes. As a result, volcanic arcs occur along lines above where the subducting plates reach a characteristic depth, typically 100 km beneath them. The location of Mount St. Helens (MSH) volcano 35–50 km in front of the main arc of volcanoes in Cascadia is puzzling and an anomaly globally. We provide the first clear image of the subducting oceanic plate beneath MSH and find it to be 68 ± 2 km deep, making this the shallowest directly imaged subducting plate beneath an arc volcano anywhere. This suggests an unusual magma pathway. The base of the North American crust, or Moho, disappears immediately to the west of MSH, indicating a close relationship between volcano location and geological processes. The geometry creates a problem in that mantle temperatures should be too low to generate magma in the mantle beneath MSH, yet the volcano occasionally erupts magmas generated in the mantle. These observations provide some of the best evidence anywhere for lateral as well as vertical transport of magma from the mantle to volcanic arcs. Key Points: The Juan de Fuca slab is imaged at 68 km without tears beneath Mount St. Helens, extremely shallow for a slab beneath an arc volcano Continental Moho signals disappear in the forearc due to both high lower-crustal velocities and hydration of the mantle wedge Magma must migrate laterally from further in the back arc or along strike to supply Mount St. Helens and surrounding forearc volcanic vents